Meta-Analysis of Risk Factors and Incidence of Interstitial Pneumonia With CHOP-Like Regimens for Non-Hodgkin Lymphoma - Yang, Jing; Chai, Limin; Jia, Junting; Su, Liping; Hao, Zhiying (Frontiers in Oncology, 2022)
Objectives: Interstitial pneumonitis (IP), a potentially fatal complication of non-Hodgkin Lymphoma (NHL) patients received CHOP (cyclophosphamide and doxorubicin and vincristine and prednisone)-like chemotherapy, negatively affected patients' clinical outcome and quality of life. We aimed to explore patient-related, disease-related and drug-related risk factors associated with IP and gain a better understanding of the incidence in NHL patients. Methods: Databases, including PubMed, Ovid, China National Knowledge Internet (CNKI), and Wanfang Database from inception to January 20, 2022, were searched to identify studies evaluating the risk factors and incidence of IP. The included studies were assessed by Newcastle-Ottawa Quality Scale and above 7 points was considered high quality. The statistical analysis of risk factors was assessed by RevMan software (version 5.3) and incidence of IP was calculated by R software (version 4.1.2). Fixed-or random-effects models were applied to estimated the relative risks (RRs) and 95% confidence interval (Cl). Results: A total of 12 studies comprised of 3423 NHL patients were included in the analysis. Among the 3 available patient-related risk factors, 6 disease-related risk factors and 3 drug-related risk factors, it was found that only drug-related risk factors were significantly associated with IP development: pegylated liposomes doxorubicin (PLD) replacement (RR = 3.25, 95% CI = 1.69-6.27, I2=64%), rituximab (RTX) addition (RR = 4.24, 95% CI = 2.58-6.96, I2=0) and granulocyte colony stimulating factor (G-CSF) administration (RR = 5.80, 95% CI = 3.05-11.05, I2=0). The pooled incidence of CHOP, R-CHOP, and R-CDOP regimen was 1.0% (95% CI 0.00-0.01, I2 = 8%), 7.0% (95% CI 0.05-0.09, I2 = 64%) and 22.0% (95% CI 0.13-0.32, I2 = 87%) respectively. Conclusion: PLD replacement, RTX addition and G-CSF administration were significant risk factors of IP for NHL patients received the CHOP-like chemotherapy. Clinicians should focus on these patients to detect and treat the IP development timely, which might bring benefit in patients' survival.